CORE STABILITY UNTUK MENINGKATKAN KESEIMBANGAN TUBUH PADA SISWA SMP NEGERI 14 PEKANBARU - Marliana; Bisra, Marido; Haryani, Yoti Sri (Awal Bros Journal of Community Development, 2025)
Body balance is a crucial component in the motor development and physical activity of adolescents. One of the key factors affecting balance is core stability, which includes the abdominal, lower back, and pelvic muscles. Unfortunately, the lack of structured physical activity among students often leads to weak core muscles, negatively impacting posture and balance. This community service program aimed to enhance the knowledge and skills of students at SMP Negeri 14 Pekanbaru in maintaining body balance through core stability training. The implementation method included education on the importance of core muscles, exercise demonstrations, and hands-on practice involving plank, crunch, hip bridge, bird dog, and bicycle exercises. The intervention was carried out over 6 weeks with a frequency of three times per week. Evaluation was conducted using the standing stork test before and after the intervention. The results showed a significant improvement in the students’ balance ability after completing the training program. Students also demonstrated high enthusiasm and a better understanding of the importance of core muscle strengthening. This activity contributed positively to improving students’ physical activity quality and serves as a practical intervention model that can be adopted by other schools. The program is expected to be sustained and integrated into the school’s physical education curriculum.